IDENTIFIKASI HAMA PADI SAWAH (Oryza sativa L) MENGGUNAKAN PERANGKAP CAHAYA DI DESA KONAROM, KECAMATAN DUMOGA TENGGARA KABUPATEN BOLAANG MONGONDOW - aputungan, Hardiana F. P; Pobela, Elva; Mokoginta, Agustinus; Bansaleng, Yessikah F.; Sugeha, Mia Audina A. (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
Research on Identification of Paddy Rice Pests Using Light Traps in Konarom Village, Southeast Dumogga District. The purpose of this study was to determine what types of nocturnal insect pests were found in rice plants in the generative phase. The research was carried out in 3 different locations, namely: 1. Konarom Village 2. West Konarom Village 3. North Konarom Village, Southeast Dumoga District, from March to July 2021. The method used in this study was descriptive analysis. Descriptive research aims to describe or explain something as it is. In the results of research conducted in the field, there are several types of insects. In Konarom Village, only 6 types of insects were found, while in Konarom Barat Village there were 7 types of insects and in North Konarom Village there were 6 types of insects. Of the 7 types of insects found, Nilaparvata lugens / Brown planthopper, the highest N value was 475 and the lowest population density was Gryllotalpa brachyptera / Orong-orong 2,5